IbM Pemanfaatan Pengolahan Limbah Biogas untuk Pupuk Organik - Yupono Bagyo; Siwi Dyah Ratnasari; Bambang Bambang (Jurnal ABM Mengabdi, 2014)
Utilization of biogas from waste management results cattle dung as organic fertilizer can be used as supporting agriculture and plantation success. Lack of knowledge society / farmers who still think that organic fertilizers can not meet the nutrition of plants and have a slower response to the biogas plant causing waste thrown away, when in fact the direct waste biogas can be used directly for organic fertilizer and organic fertilizer has a lot there advantages over other inorganic fertilizers. Hamlet Community Jambuwer Balesari Village, District ngajum Malang Regency is approximately 32.5 km from the city of Malang, live in the highlands, mostly to sustain life of farm workers and some livestock. The approach used in this IbM program are: To provide education about the advantages of organic fertilizers compared with artificial fertilizers as well as provide training to the utilization of biogas waste into organic fertilizer. IbM program that has been done, resulting in: Increasedknowledgeandawarenessof farmers/growersandcoralyouthaboutthe benefits ofbiogaswasteintoorganicfertilizerandits advantagescompared toartificialfertilizers. FarmersandKarang Tarunaable to processresidual wasteandanimal wastebiogasnonbiogasintoorganicfertilizerready to sell Trainingandmentoringof wasteutilization ofbiogasto remove the assumptionthatoneof theranchers/farmersthatlessorganicfertilizersimproveagricultural / plantation Theresultingyardsthatas a pilot areaof productive landby utilizing wastevegetablecropsbiogas. Increasethe incomeof farmers/growersofvegetables.